Bacteriology of acute otitis externa in a tertiary care centre - Sarma, Debajit; Patel, Prakash; Gohain, Mridusmita; Nath, Bijit Kumar; Payeng, Rijumoni (International Journal of Research in Medical Sciences, 2025)
Background: Acute otitis externa is a common bacterial infection of the external auditory canal, often associated with swimming or minor trauma. Understanding the bacterial communities and their antibiotic susceptibility patterns is crucial for effective treatment. Methods: This hospital-based prospective observational study included 111 patients with acute otitis externa. Aural swabs were collected, and bacterial isolates were identified through gram staining and culture and sensitivity testing. Results: The most common age group affected was 46-55 years, with a female predominance (56.76%). The most prevalent symptoms were ear pain (100%), swelling in the external auditory canal (85.58%), and otorrhea (78.37%). Gram-negative organisms (53.15%) were more common than gram-positive organisms (46.85%). Pseudomonas aeruginosa (44.82%) and Staphylococcus aureus (39.09%) were the most frequently isolated bacteria. Antibiotic susceptibility testing revealed that these organisms were susceptible to various antibiotics, including piperacillin/tazobactum, aztreonam, tobramycin, and ciprofloxacin. Conclusions: This study highlights the importance of understanding the bacterial communities and their antibiotic susceptibility patterns in acute otitis externa. Pseudomonas aeruginosa and Staphylococcus aureus were the most common isolates, and targeted antibiotic therapy can effectively treat aural infections.